Shakespeare’s Global Sonnets
XXII, 408 p. 38 illus., 4 illus. in color.
Keywords: This edited collection brings together scholars from across the world, including France, Italy, Germany, Hungary, Japan, the USA and India, to offer a truly international perspective on the global reception of Shakespeare’s Sonnets from the 18th century to the present. Global Shakespeare has never been so local and familiar as it is today. The translation, appropriation and teaching of Shakespeare’s plays across the world have been the subject of much important recent work in Shakespeare studies, as have the ethics of Shakespeare’s globalization. Within this discussion, however, the Sonnets are often overlooked. This book offers a new global history of the Sonnets, including the first substantial study of their translation and of their performance in theatre, music and film. It will appeal to anyone interested in the reception of the Sonnets, and of Shakespeare across the world. Jane Kingsley-Smith is Professor of ShakespeareStudies at the University of Roehampton, UK. She is author of three monographs: the first book-length study of the Sonnets’ reception The Afterlife of Shakespeare’s Sonnets (2019), Cupid in Early Modern Literature and Culture (2010) and Shakespeare’s Drama of Exile (2003). She is currently working on a new edition of the Sonnets for the Cambridge Shakespeare Editions series. W. Reginald Rampone, Jr. is an alumnus of Washington and Lee University, Boston College, Brown University, and the University of Rhode Island, USA. He co-edited An African Quilt: 24 Modern African Stories (2012) and is the author of Sexuality in the Age of Shakespeare (2010). He has published many book reviews in The Sixteenth-Century Journal, and is currently working on a critical edition of Shackerley Marmion's Hollands Leaguer. .